Update on Suprapubic Cystostomy Diversion vs. Primary Realignment for the Management of Blunt Posterior Urethral Injuries: A Systematic Review and Meta-Analysis - Wen, Jian-Hua; Jiang, Shao-Jun (Urology Journal, 2025)
Purpose: This paper reviewed studies comparing the effectiveness of primary urethral realignment (PUR) and suprapubic cystostomy diversion (SCD) in the early treatment of blunt posterior urethral injuries (PUI). Materials and Methods: We conducted a systematic review of original studies that directly compared the incidence of urethral strictures (US), urinary incontinence (UI), and erectile dysfunction (ED) in patients receiving primary management for pelvic fracture posterior urethral injuries with PUR versus SCD. We used Review Manager 5.3 for statistical analysis. Results: The initial search yielded 205 articles, and 14 met the inclusion criteria for the final systematic review. Meta-analysis showed that PUR was significantly more effective than SCD in reducing the proportion of US in the 365 and 335 cases of PUR and SCD, respectively (OR 0.09, 95% CI 0.04-0.22, p < 0.0001). However, there was no significant difference between PUR and SCD in the incidence of UI (OR 0.60, 95% CI 0.33-1.11) or ED (OR 0.70, 95% CI 0.45-1.11). Conclusion: PUR is more effective than SCD in reducing the incidence of US in patients with pelvic fracture posterior urethral injuries. However, there was no significant difference between PUR and SCD in the incidence of UI or ED.